2012
DOI: 10.1016/j.ygyno.2012.01.035
|View full text |Cite
|
Sign up to set email alerts
|

A brief mindfulness-based cognitive behavioral intervention improves sexual functioning versus wait-list control in women treated for gynecologic cancer

Abstract: A brief mindfulness-based intervention was effective for improving sexual functioning. Geographic restrictions permitted only a select sample of survivors to participate, thus, the generalizability of the findings is limited. Future studies should aim to develop online modalities for treatment administration to overcome this limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
1
10

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(135 citation statements)
references
References 34 publications
8
116
1
10
Order By: Relevance
“…15,16 HIV care providers need an enhanced understanding of related health issues among their clinic populations. The purpose of this study was to assess sexual function among individuals with HIV, identify relationships between sexual function and HIV parameters, and compare sexual function rates to already established literature through normative and cancer survivor cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 HIV care providers need an enhanced understanding of related health issues among their clinic populations. The purpose of this study was to assess sexual function among individuals with HIV, identify relationships between sexual function and HIV parameters, and compare sexual function rates to already established literature through normative and cancer survivor cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of expert opinion, the Working Group also recommended regular stimulation (for example, masturbation) to improve sexual response. The evidence base for this recommendation consists of six publications of low-to-moderate quality [29][30][31][32][33][34] .…”
Section: Sexual Responsementioning
confidence: 99%
“…If a woman is partnered, evidence indicates that, compared with usual care, couples-based interventions are effective. The evidence base for this recommendation consists of eight publications of low-to-moderate quality [30][31][32][33]35,37,40,41 . The studies demonstrated considerable heterogeneity with respect to target (individual, couple, group), type of counselling, number of sessions, follow-up, and outcomes measurement.…”
Section: Intimacy and Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pesar de estas evidencias, quedan cuestiones por resolver respecto a cuál es el grado de eficacia concreto que puede obtenerse aplicando el MBSR a pacientes oncológicos, puesto que los trabajos de revisión coinciden en señalar que hay bastantes limitaciones metodológicas en las investigaciones publicadas y que si el meta-análisis incluye únicamente los artículos que utilizan diseño aleatorizado, el tamaño del efecto se reduce sensiblemente (26) . Así, algunas investigaciones no utilizan la aleatorización para construir el grupo control (27) o aplican únicamente un diseño pre-post (20,28) , mientras que otras, si bien utilizan un grupo control aleatorizado, éste no recibe tratamiento, manteniéndose en lista de espera o sin recibir tratamiento específico (21,23,(29)(30)(31) por lo que es difícil concluir si el MBSR, aun siendo aparentemente eficaz, ofrece mejores resultados que otros tipos de intervención.…”
Section: Introduccionunclassified